The Teacher 's Role in the Creative Teaching of Literacy - Aladrović Slovaček, Katarina; Sinković, Željka; Višnjić, Nikolina (Croatian Journal of Education - Hrvatski časopis za odgoj i obrazovanje, 2017)
The teacher plays the central role in the educational process. In Croatian language teaching, the teacher represents a role model for his or her students in both speaking and writing. This is why it is very important to encourage teachers in language and language expression classes to stimulate and develop the creative thinking of their students by promoting new and interesting ways of finding different solutions to various problems. The creative teaching of literacy involves the use of different methods and techniques that teach students how to solve the posed problems in a creative manner (Hunt & Quaranta, 2014). Studies (Aladrović Slovaček, 2012) have shown that integration and correlation in Croatian language teaching are insufficiently used and that the level of descriptive knowledge is higher than the level of procedural knowledge. Therefore, the aim of this study is to examine the techniques and methods used in Croatian language classes in lower grades of primary school by teachers who aim to encourage the development of creative thinking in literacy teaching. Fifty (N = 50) teachers, who differ in age, years of service and attitude toward working in school, will participate in the research. It is expected that in teaching literacy, teachers use the techniques and methods that stimulate the development of creative thinking only sometimes and that these teachers perceive themselves as creative. It is also expected that younger teachers are more creative, while teachers who are more content use methods and techniques of creative thinking more frequently. Učitelj je središnja osoba odgojno-obrazovnoga procesa. U nastavi Hrvatskoga jezika učitelj je i pisani i govorni model svojim učenicima. Upravo je zato jako važno poticati učitelje da u nastavi jezika i jezičnoga izražavanja potiču i razvijaju kreativno mišljenje svojih učenika, osobito potičući traženje različitih rješenja problema na nove i zanimljive načine. Kreativno poučavanje pismenosti uključuje upotrebu različitih metoda i tehnika koje će učenike naučiti da na kreativan način rješavaju postavljene probleme (Hunt i Quaranta, 2014). Istraživanje (Aladrović Slovaček, 2012) pokazuje da su integracija i korelacija u nastavi Hrvatskoga jezika nedovoljno iskorištene te da je deklarativno znanje učenika veće od proceduralnoga. Stoga je cilj ovoga rada ispitati stavove učitelja o poticanju razvoja kreativnoga mišljenja u poučavanju pismenosti u mlađim razredima osnovne škole. U istraživanju je sudjelovalo četrdeset (N = 40) učitelja iz desetak osnovnih škola, različite dobi, različitih godina radnoga staža i različitog zadovoljstva radom u školi. Postavljene su hipoteze potvrđene jer učitelji samo ponekad rabe tehnike i metode koje potiču razvoj kreativnoga mišljenja u poučavanju pismenosti, ali sami sebe doživljavaju kreativnima. Pokazalo se također da su mlađi učitelji kreativniji, a zadovoljniji učitelji češće rabe metode i tehnike kreativnoga mišljenja.